Penerapan Pendidikan Agama Hindu Dalam Membentuk Karakter Anak di Panti Asuhan Tat Twam Asi Denpasar - Sugiantara, I Gede Yoga Pradnyana (Metta : Jurnal Ilmu Multidisiplin, 2024)
To change the character of children living in orphanages, especially in the context of implementing Hindu education, there are many challenges. They include lack of resources, shortage of sufficiently experienced teachers, the impact of the modern world and globalization, and the difficulty of maintaining correct and sustainable Hindu education within the orphanage environment. One of the main aims of research on Hindu education is to shape children's character. The use of Hindu education to influence the character of children who have lost mothers and fathers is the result of the use of special educational techniques contained in Hindu education. To address these issues, this article uses a descriptive-qualitative approach. To conduct this research, scientists are interviewed, subjects are observed directly, and information is gathered from relevant documents. Observation, interviews, and document study are data collection methods. Next, data analysis was carried out in two stages: data reduction and presentation. Then a conclusion is made. Integration of Hindu religious education at Tat Twam Asi Orphanage plays a significant role in shaping the character of the children there. It is clear that children in the orphanage have experienced positive character transformations as a result of the structured and continuously provided Hindu religious education. Hindu educational methods help develop noble qualities in children. Not all children initially show desirable traits, such as honesty, cleanliness, cooperation, and empathy, but observations and interviews show clear changes in some children. Examples of these changes include helping others, showing love to housemates, and apologizing when wrong.